Estilos de liderazgo directivo y su influencia en la gestión pedagógica en las instituciones educativas República de Venezuela y Rosa Agustina Donayre de Morey del distrito de Iquitos 2024 - Montilla Cabudiva, Lizeth (2025)
This abstract presents the main findings of a research study conducted to determine whether directive leadership styles influence pedagogical management in the República de Venezuela and Rosa Agustina Donayre de Morey educational institutions, located in the district of Iquitos, 2024.The study employed a quantitative approach and followed a correlational-causal or explanatory research design. The sample consisted of 170 school administrators and teachers from the above-mentioned institutions. The hypothesis test using Spearman's Rho statistic revealed a perfect positive correlation between the four dimensions of pedagogical leadership and the leadership style. Based on these results, it is concluded that directive leadership styles significantly influence pedagogical leadership in the República de Venezuela and Rosa Agustina Donayre de Morey educational institutions in the district of Iquitos, with a 95% confidence level.